Ketahanan Ekonomi Masyarakat Pulau-Pulau Kecil di Era Pandemi Covid-19: Kasus TWP Gili Matra - Sitti Hilyana; Saptono Waspodo; Sadikin Amir; Ayu Adhita Damayanti; Soraya Gigentika (Jurnal Ilmu Kelautan Lesser Sunda, 2022)
The Covid-19 pandemic has had a major economic impact on the community, including those on small islands. Related to this, the government as a decision maker in various programs to improve community welfare needs to think about effective and efficient forms of programs to intervene in small island communities. One of the government's basis for making these decisions is through the existing conditions of community economic resilience. Without this information and analysis regarding the existing conditions, the government will find it difficult to implement targeted intervention programs. This study aims to determine the level of economic resilience of the people of the small islands of Gili Matra as destinations that are most affected by the Covid-19 pandemic, as well as to formulate interventions that will be carried out to increase the resilience and adaptive capacity of the people of small islands in the face of the Covid-19 pandemic. The results of this study indicate that the era of the Covid-19 pandemic has had a significant impact on the economic resilience of small island communities, including the Gili Matra TWP area. During the Covid-19 pandemic, there was a weakening of business, loss of assets, loss of livelihood, loss of markets, inability to produce resulting in loss of income, so an adaptation strategy was needed to face threats and opportunities to the economic sustainability of the Gili Matra TWP community. Economic assistance for communities affected by Covid-19 is one solution in increasing the adaptability of the Gili Matra TWP community. There are five forms of intervention that need to be carried out in economic assistance, namely: 1) Strengthening/Formation of Joint Business Groups, 2) Strengthening group capacity, 3) Assistance with production equipment and production raw materials, 4) Repackaging rebranding and business nameplates, and 5) Online Marketing Training.